Pengembangan Modul Berbasis POE (Predict, Observe, and Explain) Disertai Roundhouse Diagram untuk Memberdayakan Keterampilan Proses Sains dan Kemampuan Menjelaskan Siswa Kelas X SMA Negeri 5 Surakarta (Penelitian dan Pengembangan Materi Pencemaran Lingkungan Tahun Pelajaran 2013/2014) - NURAINI, NITA; KARYANTO, PUGUH; Sudarisman, Suciati (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
The objective of this development research was to know: 1) a product- learning module based POE (Prediction, Observation and Explanation) with Roundhouse Diagram (RD) to empowering 10th grade student’s science process skills and student’s explaining abilities of State Senior High School 5 Surakarta; 2) the feasibility of module based POE with RD to empowering 10th grade student’s science process skills and student’s explaining abilities of State Senior High School 5 Surakarta; 3) the effectiveness of module based POE with RD to empowering 10th Grade student’s science process skills and student’s explaining abilities of State Senior High School 5 Surakarta. This research used Research and Development (R&D) method which refers to the development of Borg and Gall modification. The sample used in the research development are early: 1) field trial sample consisting of 6 validators; 2) The main field trial sample consisting 10 students and 1 teacher; 3) operational field trial sample consisting of 32 students. The intsrumen used in the research are questionnaire, observation, interview and test. The operational field trial used one group pretest-posttest design. Science process skills and explaining abilities data are tested by paired t-test and counted by normalized N-gain. Based on the results of research it can be concluded that: 1) the development of module based on POE with RD using a modified Borg and Gall’s development model through some steps that are research and collecting information, planning, develop a preliminary form of the product, preliminary field testing, the main product revision, playing field testing, product revision operations, field operations, final product revition, dissemination and implementation; 2) the feasibility of module based on POE with RD which is developed at the trial is categorized as good by the expert, very good by the practitioners and good by the students as well; 3) the effectiveness of module based on POE with RD is significantly increased as medium categorized in empowering science process skills and high categorized in empowering the ability to explain.